Mortality and trends of pulmonary arterial hypertension, 1990–2021: a population-based study - Jiang, Linhong; Deng, Xinliao; He, Yuchen; Ai, Yu; Li, Hui; Li, Peijun; Liu, Xiaodan (Frontiers in Cardiovascular Medicine, 2025)
BackgroundPulmonary arterial hypertension (PAH) is a progressive disease associated with high fatality rate. Comprehensive evidence concerning the epidemiology of PAH mortality is lacking. The present study aimed to assess the mortality and trends of PAH at global, regional, and national levels from 1990 to 2021.MethodsThe estimates and their 95% uncertainty interval for case number of PAH were collected from the Global Burden of Disease, Injuries, and Risk Factors Study (GBD) 2021. Age standardization by direct method was used to estimate the age-standardized mortality rate (ASMR) for PAH. We investigated the temporal trends of estimated ASMR from 1990 to 2021 and further predicted its changes in the next 15 years, decomposed the trends based on demographic factors and epidemiological changes, and quantified the cross-country health inequalities.ResultsThe global ASMR of PAH decreased from 0.35 (per 100,000 population) in 1990 to 0.27 (per 100,000 population) in 2021, with an annual percentage change of −0.82, while number of deaths increased from 14,842 in 1990 to 22,021 in 2021, an increase of 48.37%. Population growth and aging were the major drivers contributing to the number of deaths, accounting for 93.88% and 32.26%. Of note, there were significant health inequalities across 204 countries and territories, with the slope index of inequality rising over time. Projection of the global burden of PAH from 2022 to 2036 demonstrated a progressive increase in case number, but the ASMR remained largely unchanged.ConclusionPAH remains a major public health concern in some regions, particularly in high sociodemographic index region. Adequate diagnosis and targeted treatment of PAH are urgently needed to achieve a reduction in mortality.